Formulation of Legal Protection for Persons with Disabilities in The Civil Service Recruitment System in The Perspective of Human Rights - Satoto, Sukamto; Hartati, Hartati; Nazifah, Nazifah (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This research aimed to fulfill the rights of persons with disabilities to get jobs according to their fields without reducing their rights. One of them was the recruitment of civil servant candidates. The research method used was normative juridical with literature study. Decent work is a right for every human being without exception. Various racial, ethnic, and religious backgrounds that are part of human identity do not prevent him from getting his rights, likewise with the physical or non-physical conditions that underlie a human being. Every human being who has a certain physical or non-physical background also has the same right to get a decent job, including people with disabilities. The State of Indonesia has ratified the Convention on the Rights of Persons with Disabilities into Law Number 19 of 2011. In the preamble to the law, it is explained that countries that sign the Convention should promote and protect the rights and dignity of persons with disabilities and increase the participation of persons with disabilities in the civil, political fields, economic, social, and cultural-based on an equal opportunity. It means that the Indonesian government is legally obliged to fulfill the rights of persons with disabilities, especially regarding the right to work in Indonesia.